Iodo-Annulations of N-Benzyl-propiolamides Leading To Azaspiro[5.5]undecatrienones or Benzo[c]azepinones - Reddy, Chada Raji; Nagendraprasad, Thallamapuram; Islam, Jannatul; Ajaykumar, Uprety; Reddy, Cirandur Suresh; Chandrasekhar, Srivari (Synthesis, 2024)
Iodine-mediated oxidative annulations of N-benzyl-propiolamides are disclosed for the first time, providing either azaspiro[5.5]undecatrienones via dearomative ipso-annulation or benzo[c]azepinones through ortho-annulation. The selective construction of the aforementioned products is based on the ceric ammonium nitrate (CAN)-promoted divergent reactivity of the propiolamide, directed by the substituents on the phenyl ring of the N-benzyl group.
Keywords: ipso-annulation; ceric ammonium nitrate; propiolamide; dearomatization; aza-spirocycle; benzo-azepinone